2010
DOI: 10.1080/08870440802311322
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between religion and cardiovascular outcomes and all-cause mortality in the women's health initiative observational study

Abstract: Some studies suggest that religiosity may be related to health outcomes. The current investigation, involving 92,395 Women's Health Initiative Observational Study participants, examined the prospective association of religious affiliation, religious service attendance, and strength and comfort from religion with subsequent cardiovascular outcomes and death. Baseline characteristics and responses to religiosity questions were collected at enrollment. Women were followed for an average of 7.7 years and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 21 publications
4
73
2
1
Order By: Relevance
“…The absence of a relation is similar to two recent studies (Feinstein et al 2010;Schnall et al 2010), and extends the null result to the context of a collective trauma. The variability across studies and the difficulty in finding an association suggest that if there is any effect on cardiovascular ailments, it may be specific to religious or spiritual variables not measured in these studies, or that there is a moderating factor that needs to be identified.…”
Section: Physical Healthsupporting
confidence: 89%
See 1 more Smart Citation
“…The absence of a relation is similar to two recent studies (Feinstein et al 2010;Schnall et al 2010), and extends the null result to the context of a collective trauma. The variability across studies and the difficulty in finding an association suggest that if there is any effect on cardiovascular ailments, it may be specific to religious or spiritual variables not measured in these studies, or that there is a moderating factor that needs to be identified.…”
Section: Physical Healthsupporting
confidence: 89%
“…However, the evidence is not conclusive. Lower levels of religious service attendance have been related to higher rates of death from circulatory disease (e.g., Oman et al 2002), but recent work indicates that spirituality and religiosity do not relate to cardiovascular morbidity and mortality (Feinstein et al 2010;Schnall et al 2010). Little work has examined musculoskeletal ailments and religious variables.…”
Section: Physical Healthmentioning
confidence: 99%
“…The literature has clearly supported the benefits of religion on human wellbeing, while an extensive number of studies have revealed that religion has a valuable or protective effect on a variety of health outcomes (Chatters, 2000;Curlin et al, 2007;Ellison and Levin, 1998;Hall and Mdi, 2006;Jarvis and Northcott, 1987;Jones, 2004;Musick et al, 2000;Schnall et al, 2008). The predominant place of religion in health and illness was a constant theme in these studies and patients' views were strongly influenced by their religious convictions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also reported higher levels of religious involvement were associated with a reduction in cardiovascular mortality of up to 28% (Chida et al, 2009). However, such findings have not been observed among participants in two large studies of cardiovascular health, the Multi-Ethnic Study of Atherosclerosis (Feinstein, Liu, Ning, Fitchett, & Lloyd-Jones, 2010) and the Women's Health Initiative (Schnall et al, 2008). The limited available evidence also suggests that more frequent worship attendance is not associated with reductions in cancer mortality (Chida et al, 2009;Hummer et al, 1999;Oman et al, 2002).…”
mentioning
confidence: 92%
“…In the research about religious involvement and physical health, one of the most well-established findings is the existence of an inverse relationship between different measures of religious involvement and all-cause mortality (Enstrom & Breslow, 2008;Gillum, King, Obisesan, & Koenig, 2008;House, Robbins, & Metzner, 1982;Hummer, Rogers, Nam, & Ellison, 1999;Kark et al, 1996;Koenig et al, 1999;McCullough, Hoyt, Larson, Koenig, & Thoresen, 2000;Schnall et al, 2008;Strawbridge, Cohen, Shema, & Kaplan, 1997).…”
mentioning
confidence: 99%